Management of Herbal Drink Processing Lime Leaf Mistletoe - Puput Mulyono; Singgih Purnomo (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Indonesia is one of the countries that utilize plants as alternative medicine to address illnesses experienced by individuals. This research method is qualitative research, where this method is expected to produce meaning and clarity from the approach through speech, description and behavior in groups of people and institutions in the process of collecting data in the field. Herbal drinks are drinks made from natural ingredients or spices and have many health benefits for the body. Orange mistletoe leaves are often brewed into tea, which is a popular way to consume them and get their health benefits. Herbal drinks from orange mistletoe leaves are a good choice to improve health naturally. With the various benefits it offers, including antioxidant activity and antimicrobial properties, this drink can be a valuable addition to a healthy diet.